A simulation study on the manoeuvrability of a large size semitrailer - Koszałka, Grzegorz; Zniszczyński, Andrzej (Transport, 2016)
As part of a research project aimed at designing the structure of a new special-purpose multi-axle semitrailer for transporting large machines and equipment, a simulation study on the manoeuvrability of the semitrailer during its passage through a tight corner was performed. The aim of this study was to determine whether the semitrailer would meet the legal requirements regarding manoeuvrability after it has been implemented for production. The simulations were carried out using a specially designed spreadsheet. The spreadsheet enabled analysis of the movements of the wheels of the tractor-trailer combination, with the assumption that they roll without skidding; it also described changes in the steering angles of trailer wheels, as well as off-tracking and corner-cutting during turning. When the geometrical parameters of the tractor and trailer were changed, the spreadsheet allowed tracing their impact on the manoeuvrability of the whole combination. This paper presents the results of the simulations and points to the desired features of a semitrailer steering system that facilitate negotiating tight corners. First published online: 13 Jul 2015